2007
DOI: 10.2165/00044011-200727080-00004
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Patch for the Prevention of Postoperative Nausea and Vomiting

Abstract: Nicotine significantly reduced the incidence of PONV after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The difference in the incidence of vomiting by patients given placebo and those receiving ondansetron at 12 h was quite high (30 vs. 10%, p = 0.013, odds ratio 4, 95% confidence interval 1.17-8.5), but it did not reach statistical significance with the Bonferroni correction ( Table 2). On the other hand, the ondansetron group included significantly more smokers than the placebo group (Table 1) which might have affected our results since smoking has a prophylactic effect against PONV [19,20].…”
Section: Discussionmentioning
confidence: 96%
“…The difference in the incidence of vomiting by patients given placebo and those receiving ondansetron at 12 h was quite high (30 vs. 10%, p = 0.013, odds ratio 4, 95% confidence interval 1.17-8.5), but it did not reach statistical significance with the Bonferroni correction ( Table 2). On the other hand, the ondansetron group included significantly more smokers than the placebo group (Table 1) which might have affected our results since smoking has a prophylactic effect against PONV [19,20].…”
Section: Discussionmentioning
confidence: 96%
“…This effect is independent of other characteristics such as primary cancer site, treatment arm, and education. Investigations on postoperative nausea and vomiting have shown a similar finding, in which smokers experienced less incidence of the symptoms than nonsmokers . This result was not expected because tobacco and nicotine use have shown an emetogenic effect .…”
Section: Discussionmentioning
confidence: 67%
“…The association between preoperative nausea and vomiting and decreased risk of PONV identified herein is simulated by evidence indicating that cigarette smoking and preoperative nicotine patches, which are potent emetogens [10], are also associated with PONV suppression [4,11]. Sweeney [12] has suggested that the suppressive effect of smoking on PONV risk could plausibly be explained by sustained preoperative stimulation of the vomiting centers resulting in adaptation, but subsequently rejected this postulate on the basis that the emetogenic effect of smoking disappears rapidly in persistent smokers.…”
Section: Discussionmentioning
confidence: 96%